(untitled) (Journal of Hama University, 2019)
A field experiment was conducted in the farm of Abu Jarash, Olive Solid Waste (OSW) and cow manure (CM) were added to the soil at the following rates:(control, mineral fertilizer, mineral fertilizer + foliar fertilizer, fresh OSW 100%, fresh OSW 75% +CM 25%, fresh OSW 50% + CM 50%, fresh OSW 25% + CM 75%, fermented OSW100%, fermented OSW 75% + CM 25%, fermented OSW 50%+ CM 50%, OSW fermented 25% + CM 75%, 100% CM), soil fertilizer of Iron and Zinc had been add with all the previous treatments as well as the control, planting of wheat plant. Iron and Zinc forms were followed by serial extraction. The study led to the following results: fermented OSW treatment 100% has exceeded in the ratio of the following forms of iron and zinc: (Exchangeable and related with Carbonates, related with Organic matter and related with Iron Oxides and manganese) where the amount of Iron was (2.465,7.900, 40.312, 295.007) mg/kg respectively and for Zinc they were (1.5346, 6.5034, 10.7820, 21.3637) mg/kg in same previous order. The fermented OSW 75%+25 cow manure with the amount of Iron (2.135, 7.64, 36.28, 286.7) mg/kg and for Zinc they were (1.3148, 5.9811, 9.9879, 20.92) mg/kg in the same previous order.